PARTISIPASI KELOMPOK TANI DALAM KEGIATAN PENYULUHAN PERTANIAN DI DESA KANONANG LIMA, KECAMATAN KAWANGKOAN BARAT, MINAHASA - Mario Victorya Koampa; Olfie L.S. Benu; Martha M. Sendow; Vicky R.B. Moniaga (Sam Ratulangi University, 2015)
The objective of this research is to describe the participation of farmer’s group in extension activity. The benefit of this research is to support the knowledge for agricultural extension agent. This research had been conducted for three months from the the preparation to management of report from July to September, 2015 at Kanonang Lima Village Kawangkoan Barat Sub-district, Minahasa Regency. The research uses purposive random sampling of farmer;s group combined with four farmer groups namely Esa Lalan, Esa Ate, Karondoran and Berkat at Kanonang Lima Village Kawangkoan Barat Sub-district. Only two farmer groups that predominantly namely Esa Lalan and Esa Ate farmer groups. Methods of data collection is done by using the primary data. The primary data obtained directly from Esa Lalan and Esa Ate farmer groups using a list of questions. The collecting data had been conducted by using primary data from Esa Lalan and Esa Ate farmer groups. The participation of farmers’ group in agricultural activity had been classified as active at planning and conducting stage. The presence of farmer to participate in agricultural extension is needed to be increased.